Health care waste management practice in Nepal - Joshi, H D (Journal of Nepal Health Research Council, 2013)
The management of health care waste has become an urgent need to safeguard the public health from adverse effects caused due to improper management of healthcare waste. Healthcare waste management continues to present an array of challenges for developing countries, including Nepal. As the demand for healthcare facilities increases, there is also an increase in waste generation from these facilities. This situation requires an organized system of healthcare waste management to curb both public and occupational health risks. The aim of this paper is to explore the current situation of health care waste management practices in Nepal and its possible impacts on human health as well as recommend the best practices. Keywords: health impact; legislation; risk and non-risk health care waste; waste management practice.